Targeting metabolism with arsenic trioxide and dichloroacetate in breast cancer cells - Sun Ramon C; Board Philip G; Blackburn Anneke C (Molecular Cancer, 2011)
Abstract Background Cancer cells have a different metabolic profile compared to normal cells. The Warburg effect (increased aerobic glycolysis) and glutaminolysis (increased mitochondrial activity from glutamine catabolism) are well known hallmarks of cancer and are accompanied by increased lactate production, hyperpolarized mitochondrial membrane and increased production of reactive oxygen species. Methods In this study we target the Warburg effect with dichloroacetate (DCA) and the increased mitochondrial activity of glutaminolysis with arsenic trioxide (ATO) in breast cancer cells, measuring cell proliferation, cell death and mitochondrial characteristics. Results The combination of DCA and ATO was more effective at inhibiting cell proliferation and inducing cell death than either drug alone. We examined the effect of these treatments on mitochondrial membrane potential, reactive oxygen species production and ATP levels and have identified new molecular mechanisms within the mitochondria for both ATO and DCA: ATO reduces mitochondrial function through the inhibition of cytochrome C oxidase (complex IV of the electron transport chain) while DCA up-regulates ATP synthase β subunit expression. The potentiation of ATO cytotoxicity by DCA is correlated with strong suppression of the expression of c-Myc and HIF-1α, and decreased expression of the survival protein Bcl-2. Conclusion This study is the first to demonstrate that targeting two key metabolic hallmarks of cancer is an effective anti-cancer strategy with therapeutic potential.